Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for Perioperative Spine: Preoperative Nutritional Assessment. (7th September 2021) - Bisson, Erica F; Dimar, John; Harrop, James S; Hoh, Daniel J; Mohamed, Basma; Mummaneni, Praveen V; Wang, Marjorie C; Dhall, Sanjay
Abstract: BACKGROUND: Preoperative malnutrition has been implicated in adverse events after elective surgery, potentially impacting patient outcomes. OBJECTIVE: As a potentially modifiable risk factor, we sought to determine which assessments of nutritional status were associated with specific adverse events after spine surgery. In addition, we explored if a preoperative nutritional improvement intervention may be beneficial in lowering the rates of these adverse events. METHODS: The literature search yielded 115 abstracts relevant to the PICO (patient/population, intervention, comparison, and outcomes) questions included in this chapter. The task force selected 105 articles for full text review, and 13 met criteria for inclusion in this systematic review. RESULTS: Malnutrition, assessed preoperatively by a serum albumin <3.5 g/dL or a serum prealbumin <20 mg/dL, is associated with a higher rate of surgical site infections (SSIs), other wound complications, nonunions, hospital readmissions, and other medical complications after spine surgery. A multimodal nutrition management protocol decreases albumin and electrolyte deficiencies in patients with normal preoperative nutritional status. It also improves overall complication rates but does not specifically impact SSIs. CONCLUSION: It is recommended to assess nutritional status using either serum albumin or prealbumin preoperatively in patients undergoing spine surgery. The full guidelines can be accessed at https://www.cns.org/guidelines/browse-guidelines-detail/4-preoperative-nutritional-assessment .